RELATIONSHIP BETWEEN PERSONAL FACTORS AND MUTUAL FUND INVESTMENT - Mungngam, Kewalee; Thianpom, Thipsuda; Juprang, Napanut; Kongkaew, Tharitsaya (RMUTT GLOBAL BUSINESS ACCOUNTING AND FINANCE REVIEW, 2021)
The purpose of this study was to study the relationship between personal factors and interesting mutual funds of investors in Pathum Thani Province. The statistics used in the data analysis were descriptive statistics: frequency and percentage, and inferential statistics: Chi-square test. The study found that most of the respondents are female, age between 23-40 years old, graduate a bachelor's degree, work as private company employee, and earn average monthly income of 15,000-30,000 baht. Hypothesis testing results found that personal factors correlating with interesting mutual funds include age, education, income, and occupation. The related organization can differentiate promotion and program design to match with customer’s characteristics.